The case for and against export mandates for oilseeds and pulses - Ochieng, Dennis O.; Baulch, Bob (International Food Policy Research Institute, 2020)
An export mandate means that exports can only be made through a structured market, such as a commodity exchange or a formal trading floor/platform where agricultural value chain actors (farmers, commodity exchanges, millers, processors, exporters) conduct organized, regulated trade, usually with specific financial arrangements. In Malawi, a singular example is the tobacco export mandate which has existed for over 70 years with a formal and organized market structure through the auction floors. Only a few other African countries also have export mandates, including Ethiopia (coffee and sesame) and Rwanda (coffee and tea). Some West African countries also only permit exports of cotton through their state marketing boards.